2022
DOI: 10.1186/s12915-022-01246-x
|View full text |Cite
|
Sign up to set email alerts
|

Bex1 is essential for ciliogenesis and harbours biomolecular condensate-forming capacity

Abstract: Background Primary cilia are sensory organelles crucial for organ development. The pivotal structure of the primary cilia is a microtubule that is generated via tubulin polymerization reaction that occurs in the basal body. It remains to be elucidated how molecules with distinct physicochemical properties contribute to the formation of the primary cilia. Results Here we show that brain expressed X-linked 1 (Bex1) plays an essential role in tubulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Brain-expressed X-linked 1 ( BEX1 ) belongs to the BEX gene family, which consists of BEX1 , BEX2 , BEX3 , BEX4 , Tceal1 , Tceal3 , Tceal5 , Tceal6 , Tceal7 , Tceal8 , and Tceal9 [ 16 ]. In agreement with our findings, AronowBJ et al found that BEX1 showed upregulated expression levels in the hearts of mice with heart failure [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain-expressed X-linked 1 ( BEX1 ) belongs to the BEX gene family, which consists of BEX1 , BEX2 , BEX3 , BEX4 , Tceal1 , Tceal3 , Tceal5 , Tceal6 , Tceal7 , Tceal8 , and Tceal9 [ 16 ]. In agreement with our findings, AronowBJ et al found that BEX1 showed upregulated expression levels in the hearts of mice with heart failure [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression analysis across GE-SCJ epithelial cell clusters unraveled the gene expression signature associated with embryonic precursor epithelial cells (Sox11, Igf2, H19, Cldn6, Vcan, and Bex1) [18][19][20][21][22][23][24] committing to either the squamous (Trp63, Col17a1, Krt5, Krt15, Krt13, Lgals7) or columnar (Muc5b, Furin, Pgc, Muc6, Agr2) epithelial lineages (Fig. 1f, g, and Supplementary Data 2).…”
Section: Single-cell Map Of Epithelial Lineage Development At the Ge-scjmentioning
confidence: 99%